Quality Investment and Price Formation in the Performing Arts Sector: A Spatial Analysis - Stefan Traub (Kiel University, Department of Economics, 2005)
In this paper, we present a spatial model of the public provision of the performing arts. Agents behave boundedly rational. Art directors set performance quality according to their aspiration levels. While taking into account the spatial distribution of the population, administrative directors in calculating ticket prices ignore that they compete with neighboring performing arts organization (PAOs) for audience. The model is tested empirically using a spatial autoregressive (SAR) model with a complete data set of German PAOs and cities. Our data support the model and help to explain the size and distribution of losses in the public performing arts sector.
Keywords: Z10; H41; R59; 330; Performing Arts; Local Public Goods; Quality; Spatial Competition; Bounded Rationality; Theater; Musikwirtschaft; Lokales öffentliches Gut; Dienstleistungsqualität; Administrierter Preis; Räumlicher Wettbewerb; Beschränkte Rationalität; Theorie; Deutschland